Arterivenous malformation of the cerebellopontine angle - Rodríguez Juanotena, Jorge; Benedek, Pedro; Bastarrica, Ernesto; Estable, Miguel; de Tényi, Andrés (Cirugía del Uruguay, 1978)
An exceptional case of arteriovenous malformation of the cerebellopontine angle -successfully treated by microneurosurgical technique- is described.